A Study of the Strategic Responses of Commercial Banks to Changes in the External Environment in Zambia - Kamiji Ndonji; Lubinda Haabazoka (International Journal of Engineering and Management Research, 2024)
Banking sectors play a crucial part in the growth of an economy. As a result, the banking sector's stability is critical to an economy's growth. Commercial banks are faced with external environmental changes that may render negative as well as positive impacts on commercial banks. Strategic management is one of the key corner stones of any business institution that needs to compete favourably in a particular industry and respond to changes in the external environment. Crafting strategies to suit changes in the external environment is one principal goal of every organisation whose aim is to remain competitive in the market, generate profits and attain growth. This investigated response strategies to external environment (economic changes, technological changes, and social-culture changes) of commercial banks in Zambia. Descriptive research approach was used with 38 questionnaires distributed. Only 20 questionnaires were returned and correctly answered, representing 52.6% response rate, enough to draw conclusions and recommendations. Data analysed quantitatively in SPSS and Microsoft excel with result values presented using percentages, averages, and means. The results revealed that commercial banks did not respond to social-cultures changes in consumer behaviour in Zambia. However commercial banks responded to economic and technological factors, which led to closure of some branches and bank merges. To that end, commercial banks adopted various response strategies to respond to the changes. Strategies adopted included stability and expansion while no commercial bank adopted retrenchment strategy. Commercial banks should not only concentrate on stability strategies, but also use other strategies such as expansion and retrenchment strategies to survive the harsh external turbulence. Management of commercial banks should take advantage of advances in information and communication technology that enhances service delivery and meeting customer needs. Banks need to constantly scan the environment using various tools like SWOT, Research and Development and PESTEL in order to be aware of changes in the external environment and prepare for it.